Utilization of Gadgets in Improving Students' Learning Abilities in The History Subject of Grade X at SMA Labschool of Tadulako University - Rifa; A Rore, Idrus; M Gamar, Mahfud (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The problems in this research article are: How can the use of gadgets improve students' learning abilities in history subjects for class X SMA Labschool UNTAD? and b What are the positive and negative impacts of using gadgets in UNTAD Labschool High School The aim of this study is to describe the use of gadgets to improve students' learning abilities in history subjects in grade X at SMA Labschool Untad and to explain the positive and negative impacts of gadget use. The method used is descriptive qualitative. The results of this study indicate that: (1) The use of gadgets as a tool is very effective in supporting the learning process in the classroom. (2) The positive and negative impacts of using gadgets have a significant influence on students' learning abilities. Therefore, it can be concluded that the use of gadgets has the potential to improve and weaken students' abilities in following the learning process in the classroom.